2012
DOI: 10.1093/humrep/des299
|View full text |Cite
|
Sign up to set email alerts
|

The ENDOCARE questionnaire guides European endometriosis clinics to improve the patient-centeredness of their care

Abstract: This work was funded by KU Leuven and European Network of Endometriosis (ENE), supported by the European Commission (Public Health Executive Agency). No competing interests are declared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(53 citation statements)
references
References 64 publications
5
46
2
Order By: Relevance
“…Specialized tertiary endometriosis clinics aiming to identify clinic-specific targets for patient-centered improvement projects could use the published, freely available ENDOCARE questionnaire developed by our group based on insights from this review and validated and reliable for Europe [24,63]. The ENDOCARE questionnaire meets the 8 methodological requirements for questionnaires [21,64], evaluates the 10 dimensions of patient-centered endometriosis care and allows the identification of improvement targets [24].…”
Section: Discussionmentioning
confidence: 99%
“…Specialized tertiary endometriosis clinics aiming to identify clinic-specific targets for patient-centered improvement projects could use the published, freely available ENDOCARE questionnaire developed by our group based on insights from this review and validated and reliable for Europe [24,63]. The ENDOCARE questionnaire meets the 8 methodological requirements for questionnaires [21,64], evaluates the 10 dimensions of patient-centered endometriosis care and allows the identification of improvement targets [24].…”
Section: Discussionmentioning
confidence: 99%
“…Obstetric-gynecological history. The obstetric-gynecological history investigated: any use of hormonal contraceptives, the reason why they are taken, any previous abortion, pregnancy, the age at which the menstrual cycle began, its regularity, frequency, the heaviness and length of menstrual bleeding, dysmenorrhea, any consequence on usual daily life, painful defecation during menstrual cycle, dyspareunia and chronic pelvic pain unrelated to the menstrual cycle [40]. Some studies showed that women who have endometriosis are more likely to have experienced premature menarche and more regular and shorter menstrual cycles, with more massive and longer bleeding than controls [41].…”
Section: Questionnaire Designmentioning
confidence: 99%
“…In women with endometriosis, patient-centredness can be measured with the ENDOCARE questionnaire (ECQ), which has been validated in tertiary care centres ( Dancet et al , 2011 , 2012 ). The current study aimed to investigate patient-centredness of endometriosis care in a secondary care setting and a tertiary care setting and aimed to investigate how patient-centredness can be improved.…”
Section: Introductionmentioning
confidence: 99%